ChemInform Abstract: Li18Na2Ge17 — A Compound Demonstrating Cation Effects on Cluster Shapes and Crystal Packing in Ternary Zintl Phases. Issue 16 (22nd April 2014) - Scherf, Lavinia M.; Zeilinger, Michael; Faessler, Thomas F.
Abstract The new title compound is synthesized from a stoichiometric mixture of the constituent elements (tantalum ampule, 750 °C, 1 h) and characterized by single crystal XRD and magnetic measurements.